Peningkatan Motivasi Belajar Siswa Melalui Metode Pembelajaran pada Mata Pelajaran Bahasa Indonesia di SMAN 1 Sukaraja, Kabupaten Sukabumi - Christine Lorenzi; Farah Mayla Shafa; Thasya Dwi Putri; Tsabita Nawal Sabilla Hidayah (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Motivation and learning are two things that are interrelated and influence each other. Through the learning process, teachers are required to be able to guide and facilitate students to motivate them to carry out learning activities. The success of a student in learning is determined by many factors, one of which is learning motivation. One of the steps that can be taken to facilitate student learning activities is through the use of varied learning methods, including: (1) lectures; (2) discussions; (3) simulations; (4) project-based learning; (5) problem- based learning; (6) demonstrations; (7) games and many other methods. At the high school level, Indonesian language subjects are focused on developing the character of critical thinking to creativity. The variety of learning methods is very influential in efforts to motivate students to the lessons taught. In this study using data collection techniques by using a questionnaire made using Google Form with a total of 74 respondents, class XII as much as 52.7%, class XI 33.8%, and class X 13.5%. Through this research, the extent to which students are familiar with learning methods and their implications for learning motivation in Indonesian language subjects at SMAN 1 Sukaraja, Sukabumi District.